Hubugan Panjnag Tungkai Dan Kekuatan Otot Tungkai Dengan Jauhnya Tendangan Dalam Permaian Sepakbola Pada Siswa MA Babang Halmahera Selatan - Suhardi, M. Ikra; Saiman, Rifaid (Jurnal Ilmiah Wahana Pendidikan, 2025)
This study aims to determine the relationship between leg length and leg muscle explosive power with the distance of kicks in football games in MA Babang Halmahera Selatan students. This study is a correlational research design. The subjects of the study were MA Babang Halmahera Selatan students. The data sources came from tests and measurements. The results of the study showed that: 1) leg length with the distance of kicks in football games in MA Babang Halmahera Selatan students obtained an r-count value of 0.984 and a sig. value of 0.000. Because the sig. value = 0.000 <α = 0.05, then there is a relationship between leg length and the distance of kicks in football games in MA Babang Halmahera Selatan students. 2) leg muscle explosive power with the distance of kicks in football games in MA Babang Halmahera Selatan students obtained an r-count value of 0.964 and a sig. value of 0.000. Because the sig. value = 0.000 <α = 0.05. then there is a relationship between leg muscle explosive power and the distance of kicks in football games in MA Babang Halmahera Selatan students. 3) leg length and leg muscle explosive power with the distance of kicks in football games in MA Babang Halmahera Selatan students obtained the r-count value of 0.984 and the sig. value is 0.000. Because the sig. value = 0.000 <α = 0.05. then there is a relationship together between leg length and leg muscle explosive power with the distance of kicks in football games in MA Babang Halmahera Selatan students. The conclusions of this study are 1) there is a relationship between leg length and the distance of kicks in football games in MA Babang Halmahera Selatan students. 2) There is a relationship between leg muscle explosive power and the distance of kicks in football games in MA Babang Halmahera Selatan students. 3) there is a relationship together between leg length and leg muscle explosive power with the distance of kicks in football games in MA Babang Halmahera Selatan students.